Reverse swing‐M, phase 1 study of repurposing mebendazole in recurrent high‐grade glioma. (13th May 2020) - Patil, Vijay M.; Bhelekar, Arti; Menon, Nandini; Bhattacharjee, Atanu; Simha, Vijai; Abhinav, Ram; Abhyankar, Anuja; Sridhar, Epari; Mahajan, Abhishek; Puranik, Ameya D.; Purandare, Nilendu; Janu, Amit; et al.
Abstract: Background: Relapsed high‐grade glioma has dismal outcomes. Mebendazole has shown promising activity against glioma in in‐vitro and in‐vivo studies. Hence, we undertook a phase 1 study to repurpose mebendazole in the treatment of glioblastoma. Methods: We conducted a phase 1 study (accelerated titrated design 4) of mebendazole in patients with recurrent glioblastoma (GBM). Patients eligible for re‐irradiation were enrolled in arm A1 (radiation with concurrent temozolomide 75 mg/m 2 daily during the course of radiation+mebendazole) while patients who were ineligible were enrolled in either arm B1 (CCNU 110 mg/m 2 day 1, every 6 weekly + mebendazole) or arm C1 (temozolomide 200 mg/m 2 day 1‐5, every 4 weekly + mebendazole). The primary endpoint of phase 1 was to identify the MTD of mebendazole in each combination. Findings: 11 patients were enrolled in the whole study. MTD of mebendazole was not reached in arm A1 and C1 and hence the recommended dose for phase 2 was 1600 mg TDS (4800 mg) per day. The MTD of mebendazole in combination with CCNU was 1600 mg TDS (4800 mg) per day and the dose recommended for phase 2 was 800 mg TDS (2400 mg) per day. The three most common adverse events seen in the study were anemia (n = 9, 81.8%), nausea (n = 7, 63.6%), and fatigue (n = 6, 55.5%). Interpretation: The recommended phase 2 dose of mebendazole is 1600 mg TDS with temozolomide and temozolomide‐radiation combination while the dose of 800 mg TDS needs to be used with single‐agent CCNU. Abstract : This was a phase 1 study in relapsed recurrent glioma for repurposing Mebendazole. The recommended dose identified for future studies for mebendazole in adult glioma patients was 4800 mg per day with both temozolomide‐radiation and single‐agent temozolomide while it was 2400 mg with CCNU.